Bacterial Ligase D preternary-precatalytic complex performs efficient abasic sites processing at double strand breaks during nonhomologous end joining - de Ory, Ana (Nucleic Acids Res, 2019)
Abasic (AP) sites, the most common DNA lesions are frequently associated with double strand breaks (DSBs) and can pose a block to the final ligation. In many prokaryotes, nonhomologous end joining (NHEJ) repair of DSBs relies on a two-component machinery constituted by the ring-shaped DNA-binding Ku that recruits the multicatalytic protein Ligase D (LigD) to the ends. By using its polymerization and ligase activities, LigD fills the gaps that arise after realignment of the ends and seals the resulting nicks. Here, we show the presence of a robust AP lyase activity in the polymerization domain of Bacillus subtilis LigD (BsuLigD) that cleaves AP sites preferentially when they are proximal to recessive 5′-ends. Such a reaction depends on both, metal ions and the formation of a Watson–Crick base pair between the incoming nucleotide and the templating one opposite the AP site. Only after processing the AP site, and in the presence of the Ku protein, BsuLigD catalyzes both, the in-trans addition of the nucleotide to the 3′-end of an incoming primer and the ligation of both ends. These results imply that formation of a preternary-precatalytic complex ensures the coupling of AP sites cleavage to the end-joining reaction by the bacterial LigD.